A case of prosthetic valve endocarditis and aortic abscess due to Bacillus cereus - Akina Fukushima; Takaaki Kobayashi; Yoshihito Otsuka; Naoto Hosokawa; Sandra Moody; Miyu Takagi; Akihito Yoshida (IDCases, 2024)
Bacillus cereus (B. cereus) is commonly found in the environment and is often considered a blood culture contaminant. However, in patients with specific risk factors such as intravenous drug use, central venous access catheters, immunosuppression, or prosthetic valves, B. cereus can cause severe infections. Herein, we present a case of prosthetic valve endocarditis (PVE) caused by B. cereus in an 84-year-old woman with a history of aortic valve replacement for aortic stenosis five years earlier. She presented with anorexia, and her physical examination revealed tenderness in the left upper quadrant of the abdomen. Blood culture grew B. cereus, and a CT scan showed splenic infarction, raising suspicion of PVE. Transesophageal echocardiogram (TEE) revealed an abscess around the left coronary cusp of the aortic valve and a 15 mm vegetation. Due to the patient's high risk for post-operative complications and her unwillingness to undergo surgery, the surgery was deferred. Instead, she was successfully treated with six weeks of intravenous vancomycin and discharged home. Follow-up TEE demonstrated resolution of the vegetation and valvular abscess. At her six-month post-discharge evaluation, no signs of active infection were noted including fever or worsening heart failure. Although surgery is typically recommended for most cases of PVE, conservative treatment can be considered as an alternative option for selected patients.